Acoustic properties of periodic micro-structures obtained by additive manufacturing. (May 2019) - Fotsing, Edith Roland; Dubourg, Arnaud; Ross, Annie; Mardjono, Jacky
Abstract: Periodic acoustic structures of rigid micro-rods produced via additive manufacturing were analyzed using an impedance tube in the 500 Hz–6000 Hz frequency range. The acoustical properties such as the porosity, the airflow resistivity, the tortuosity, the viscous characteristic length and the thermal characteristic length were determined by comparing an analytical model and the experimental results. The model which takes into account the interaction between the acoustic wave and a rigid periodic structure was proven to be an effective tool to correlate the final acoustic performance of the structure and the printing parameters. It was shown that broadband acoustic capabilities can be improved over the studied frequency range with the smallest filament possible or by reducing the lattice parameter and/or by changing the orientation of the filament from one layer to the next. This work was motivated by the need to control the manufacturing parameters of acoustic materials with broadband absorption capabilities. Furthermore the present investigation paves the way to explore new avenues to replace stochastic porous materials by new structures with combined mechanical and acoustic properties.